Rural seed sector development through participatory varietal selection - Wilkus, Erin Lynn; Francesconi, Gian Nicola; Jäger, Matthias (Emerald, 2017)
Purpose This impact assessment provides empirical evidence from household producer surveys to test the assumptions surrounding the contribution of participatory varietal selection (PVS) activities on seed sector development. The purpose of this paper is to focus on household access and adoption of common bean varieties from seed provision services and local markets to determine if, and under what social conditions, PVS activities stimulated seed uptake and market participation. Design/methodology/approach The propensity score matching technique and simple regression analysis were used to estimate the impact and compare household performance across three farmer groups located in Hoima, Uganda. Findings PVS increased access to and adoption of improved varieties and supported additional intermediate development outcomes when farmer group characteristics were aligned with PVS efforts. Specifically, PVS was more likely to stimulate market purchases of newly introduced varieties in the farmer group located closest to markets. The project did not however, improve all the development objectives that were evaluated. PVS most critically, did not increase the probability that households received the specific varieties they desired. Research limitations/implications This study found that PVS can support the key pillars of seed sector development. In addition to increasing household access to new varieties, free seed dissemination promoted market participation and stimulated local seed market development. Originality/value This study addressed the need to consider intermediate development outcomes in impact assessments of development interventions. The findings clarified the contribution of PVS in the context of broader development goals and identified farmer group dynamics associated with enhanced impacts among rural producers in Uganda.